ANALISIS PERAN GANDA WANITA TERHADAP KESEJAHTERAAN DI SUMATERA BARAT - Tria Agustin; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to analyze the influence of factors (X1) Wife's working hours on welfare, (X2) Wife's last education on welfare, (X3) Husband's last education on welfare in West Sumatra. This study uses the logistic regression method. The sample used was taken from prosperous households based on per capita expenditure in West Sumatra. This study uses Susenas West Sumatra Province data in 2015. The results of the study show that (1) wife's working hours have a significant effect on welfare. (2) Last wife education has a significant effect on welfare. (3) Husband's last education has a significant effect on welfare. (4) Taken together there are significant effects between wife's working hours, wife's last education, and husband's last education on welfare in West Sumatra. From the results of research, Welfare and the dual role of women generally have a positive relationship or relationship. Especially for prosperous households. Households whose wives are involved in earning a living will tend to be more prosperous than households whose wives do not play a role in earning a living, so special attention from the government is needed to provide job training for wives to have skills so that they can play an active role in economy and impact on households that tend to be more prosperous.